Atypical Presentation of Pseudoxanthoma Elasticum in Two Siblings from North India - Sunayana Misra; Ravindra Kumar Saran (Acta Medica, 2020)
Pseudoxanthoma elasticum (PXE) is a rare hereditary disorder occurring due to metabolic defect in the liver and manifesting predominantly in the skin, eyes and arteries. It shows characteristic yellowish papules on the skin around the nape of neck along with looseness of skin over flexural surfaces. PXE shows marked phenotypic heterogeneity. Complications related to arterial wall and retinal Bruchs’ membrane calcification occur later in life; early diagnosis therefore helps keep patient on follow up for development of the same. In Indian patients, classic skin changes may be missed clinically making histopathology pivotal in diagnosis and patient management.